Confirmation of Pig-a mutation in flow cytometry-identified CD48-deficient T-lymphocytes from F344 rats - Revollo, Javier; Pearce, Mason G.; Petibone, Dayton M.; Mittelstaedt, Roberta A.; Dobrovolsky, Vasily N. (Mutagenesis, 2015)
The Pig-a assay is used for monitoring somatic cell mutation in laboratory animals and humans. The assay detects haematopoietic cells deficient in glycosylphosphatidylinositol (GPI)-anchored protein surface markers using flow cytometry. However, given that synthesis of the protein markers (and the expression of their genes) is independent of the expression of the X-linked Pig-a gene and the function of its enzyme product, the deficiency of markers at the surface of the cells may be caused by a number of events (e.g. by mutation or epigenetic silencing in the marker gene itself or in any of about two dozen autosomal genes involved in the synthesis of GPI). Here we provide direct evidence that the deficiency of the GPI-anchored surface marker CD48 in rat T-cells is accompanied by mutation in the endogenous X-linked Pig-a gene. We treated male F344 rats with N-ethyl-N-nitrosourea (ENU), and established colonies from flow cytometry-identified and sorted CD48-deficient spleen T-lymphocytes. Molecular analysis confirmed that the expanded sorted cells have mutations in the Pig-a gene. The spectrum of Pig-a mutation in our model was consistent with the spectrum of ENU-induced mutation determined in other in vivo models, mostly base-pair substitutions at A:T with the mutated T on the non-transcribed strand of Pig-a genomic DNA. We also used next generation sequencing to derive a similar mutational spectrum from a pool of 64 clones developed from flow-sorted CD48-deficient lymphocytes. Our findings confirm that Pig-a assays detect what they are designed to detect-gene mutation in the Pig-a gene.